2020
DOI: 10.1038/s41562-020-0889-7
|View full text |Cite
|
Sign up to set email alerts
|

How behavioural sciences can promote truth, autonomy and democratic discourse online

Abstract: Public opinion is shaped in significant part by online content, spread via social media and curated algorithmically. The current online ecosystem has been designed predominantly to capture user attention rather than to promote deliberate cognition and autonomous choice; information overload, finely tuned personalization and distorted social cues, in turn, pave the way for manipulation and the spread of false information. How can transparency and autonomy be promoted instead, thus fostering the positive potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 101 publications
(97 reference statements)
1
132
0
2
Order By: Relevance
“…If this explanation is correct, then in order for privacy concerns and behavior to match more closely, the data privacy functions of online services should be more accessible, explained in simpler terms, and easy to use. Behavioral interventions (e.g., digital nudging and boosting; see 26,27) can also be employed to empower users to align their privacy protective measures to their level of privacy concern. New transparency measures could enable people to exercise their preferences in a more nuanced way; this would be an important next step towards regaining autonomy in the online world.…”
Section: Discussionmentioning
confidence: 99%
“…If this explanation is correct, then in order for privacy concerns and behavior to match more closely, the data privacy functions of online services should be more accessible, explained in simpler terms, and easy to use. Behavioral interventions (e.g., digital nudging and boosting; see 26,27) can also be employed to empower users to align their privacy protective measures to their level of privacy concern. New transparency measures could enable people to exercise their preferences in a more nuanced way; this would be an important next step towards regaining autonomy in the online world.…”
Section: Discussionmentioning
confidence: 99%
“…Boosting cognitive competencies online by redesigning the environment might involve changing the way information is presented to users or providing additional cues to existing information to improve the epistemic quality of online content (Lorenz-Spreen, Lewandowsky, et al, 2020). For example, such informational boosts can draw on research in algorithmic detection of false rumors; for example, Vosoughi et al (2017) identified three categories of cues predictive of the veracity of online information (in this case, information shared on Twitter): people (who spreads the news), linguistic content (what words are used), and propagation dynamics (the shape of an information cascade).…”
Section: Behavioral Interventions Online: Nudging Technocognition Amentioning
confidence: 99%
“…These websites also take advantage of the asymmetry of knowledge and difference in expertise between the writers and the readers to help the spreading their rumor. Asymmetry of knowledge and difference in expertise refers to the gap in the level of knowledge between the writer and the reader in a given subject, which makes a reader believe the website is a reliable source, instead of questioning its legitimacy (Lorenz-Spreen, Lewandowsky, Sunstein, & Hertwig, 2020;Clarkson, Jacobsen, & Batcheller, 2007).…”
Section: Motivated Reasoning and Asymmetry Of Knowledgementioning
confidence: 99%
“…When one reads something on social media, they can choose to share it with their followers, and their followers can choose to do the same. This reposting cycle is known as the rumor cascading effect, and it increases the speed of the spread of misinformation (Lorenz-Spreen, Lewandowsky, Sunstein, & Hertwig, 2020). Source monitoring, on the other hand, refers to the tendency for readers to remember solely the content of an article or other forms of media, and ignores or misremembers the source of said media (Dywan & Jacoby, 1990).…”
Section: Social Mediamentioning
confidence: 99%
See 1 more Smart Citation